Effect of Boron Sinter-Aid on the Microstructure and Properties of Austenitic Stainless Steel- TIB2 Composites / Wpływ Dodatku Boru Na Mikrostrukturę I W Łaściwosci Kompozytów Stal Austenityczna-TIB2 - Sulima I.; Jaworska L.; Karwan-Baczewska J. (Archives of Metallurgy and Materials, 2015)
In the work, the effect the boron addition on the microstructure and properties of the composites with austenitic steel of matrix was investigated. The composites were consolidated using the high pressure-high temperature (HP-HT) method. Two composite types were fabricated, i.e. steel with 8 vol.% TiB2 and steel with 8 vol.% TiB2 and 1 vol.% boron. Density of sintered materials was measured according to the Archimedes principle. Mechanical properties were determined by Vickers microhardness and compression test. The wear resistance was investigeted using ball-on-disc method. The microstructure of composites was analyzed using a scanning electron microscope.